Interpretation of the Fast Tarawih Prayer Tradition by the Congregation: A Living Qur'an Study at Mantenan Islamic Boarding School in Blitar - Cholid Ma'arif; Ahmad Fathurrobbani; Abdul Natsir (QOF, 2023)
This article aimed to uncover the meaning behind the phenomenon of fast tarawih prayers that are traditionalized at the Mantenan Islamic Boarding School during Ramadan. The uniqueness of the fast tarawih prayer lies in the speed of the prayer movement which is considered unusual, so that tarawih can be completed in approximately ten minutes. This phenomenon is often the subject of news among Indonesian Muslims and digital media every time the holy month of Ramadan enters. This research belongs to the scope of living Qur'an studies and field research where data is obtained based on field searches through observation, interviews, and documentation studies. To analyze the phenomenon, the researcher used Karl Mannheim's sociology of knowledge theory. The results of the study reveal that: First, the fast tarawih congregation of Pondok Mantenan has been carrying out this practice for generations because it has been traditionalized by the pioneering figures of the pesantren. Furthermore, this becomes a practice that corresponds to the pragmatic needs of the congregation. Second, the understanding of religious leaders and fast tarawih pilgrims of the verse of the virtue of Ramadan and night prayers as well as the hadith of alleviating congregational prayers and the virtue of the majlis of knowledge over sunnah prayers is realised as a form of syiar reviving the night of Ramadan through the practice of fast tarawih. Thirdly, the meaning of verses and hadiths that support the practice of fast tarawih is based on the principle of maintaining the instant cultural reality of the community wrapped in religious traditions.